Recurrent pre‐eclampsia in women with metabolic syndrome and low plasma volume: a retrospective cohort study. (December 2015) - Stekkinger, E; Scholten, RR; Heidema, WM; Spaanderman, MEA
Abstract : Objective: To determine the prevalence of recurrent pre‐eclampsia in women with a history of pre‐eclampsia with both metabolic syndrome and low plasma volume postpartum, as compared with women without either entity. Design: Retrospective cohort study. Setting: Three tertiary referral hospitals in the Netherlands. Population: Women with a history of pre‐eclampsia. Methods: In 196 women with a history of pre‐eclampsia we determined the presence or absence of metabolic syndrome using the World Health Organization criteria and measured plasma volume with the 125 I‐human serum albumin indicator dilution technique. We compared the prevalence of recurrent pre‐eclampsia in four groups, classified according to presence or absence of metabolic syndrome and low or normal plasma volume, calculating odds ratios (OR), adjusted for confounders. Main outcome measure: Recurrence of pre‐eclampsia in the subsequent pregnancy. Results: The prevalence of recurrent pre‐eclampsia was 12% (12/99) in women without metabolic syndrome with normal plasma volume, versus 47% (8/17) in women with both metabolic syndrome and low plasma volume: OR 6.44 (95% CI 2.09–19.90), adjusted OR 7.90 (95% CI 2.30–27.16). Recurrent pre‐eclampsia was present in 44% (10/23) and 25% (14/57) of women with isolated metabolic syndrome and low plasma volume, respectively. Conclusions: In the concomitant presence of metabolic syndrome and low plasma volume, the prevalence of recurrent pre‐eclampsia was nearly 50%, which is four times as high as the prevalence in women without either entity. Tweetable abstract: Metabolic syndrome and low plasma volume raise the risk of recurrent pre‐eclampsia to nearly 50%. Tweetable abstract: Metabolic syndrome and low plasma volume raise the risk of recurrent pre‐eclampsia to nearly 50%.